Mexiko als Geliebte – Europas literarische Conquista: Über einen Sehnsuchtsort in der deutschsprachigen Literatur - Kodym, Caroline (transcript, 2020)
As a Eurocentric projection surface for European (primal) longings, mental images and social utopias, Mexico is conquered literarily as the lover of Europe.